SOSIALISASI SIA PELAPORAN AKUNTANSI UMKM MAGANG MAHASISWA MBKM UNIVERSITAS INDO GLOBAL MANDIRI - Allya, Veni; Hertati, Lesi; Terrtiavini, Terrtiavini; Heryati, Agustina; Cahyani, Nani; Puspitawati, Lilis (Transpublika Publisher, 2024)
Through Indo Global Mandiri University's Student Internship program (MBKM), the socialization of Accounting Information Systems (AIS) both traditional and based on the latest technology has made an important contribution in increasing students' understanding and acceptance of the importance of AIS in banking. Increased Understanding: Participation in the internship program has increased students' understanding of AIS both traditional and current technology-based. The important role of AIS in supporting appropriate decision making in banking activities. The MBKM internship program has proven effective in socializing AIS to students. Through various socialization methods such as hands-on training, workshops, and the use of technology, students can gain a comprehensive understanding of AIS. The socialization of AIS based on the latest technology also provides additional benefits, such as real-time access capabilities, better collaboration, and more accurate data analysis. This strengthens students' understanding of the importance of technology in improving the efficiency and effectiveness of accounting processes. Nevertheless, there are challenges that need to be overcome in the AIS socialization process, such as the diverse level of understanding among students and the limited time in delivering the material. However, by continuing to improve socialization methods and adapting more sophisticated technology, opportunities to strengthen understanding and acceptance of AIS are increasingly wide open.